2021
DOI: 10.1038/s41531-021-00222-6
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson’s disease patients benefit from bicycling - a systematic review and meta-analysis

Abstract: Many Parkinson’s disease (PD) patients are able to ride a bicycle despite being severely compromised by gait disturbances up to freezing of gait. This review [PROSPERO CRD 42019137386] aimed to find out, which PD-related symptoms improve from bicycling, and which type of bicycling exercise would be most beneficial. Following a systematic database literature search, peer-reviewed studies with randomized control trials (RCT) and with non-randomized trials (NRCT) investigating the interventional effects of bicycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Indeed, in idiopathic Parkinson’s disease physical exercise helps improving motor outcomes, i.e. reducing bradykinesia ( Tiihonen et al, 2021 ). Similarly, anecdotal reports in chronic catatonia suggest beneficial effects of physical exercise ( Heckers and Walther, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in idiopathic Parkinson’s disease physical exercise helps improving motor outcomes, i.e. reducing bradykinesia ( Tiihonen et al, 2021 ). Similarly, anecdotal reports in chronic catatonia suggest beneficial effects of physical exercise ( Heckers and Walther, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…No high-quality systematic review evidenced benefit of non-motor outcomes by aerobic exercises ( Table 4 ). Even so, moderate quality studies found improvement in quality of life after performing aerobic exercise protocols [ 25 , 26 ]. Protocol registration prior to commencement of the review and adequate literature search were the critical domains that lowered rating of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…Since patients with PD have a decreased balance ability in the advanced stage, a bicycle is advantageous in that it can be applied more safely than a treadmill in patients with reduced balance ability. A meta-analysis including 505 PD patients in 2021 demonstrated that bicycling led to improvement in physical functionality, gait speed, balance, and QOL in patients with PD [ 9 ].…”
Section: Rehabilitation For Motor Functionmentioning
confidence: 99%